"Some(where)…Some(how)…Some(time)": detecting elements of racist ideology by analyzing the time and space of narrative - Κουτζιακουτζίδου Θεοδώρα (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2016)
The aim of this paper is to analyze time and space of narration in two illustrated books, “A Special Friend-it all started with a yellow bike” (2010) by Anny Theochari, illustrated by Willy Karabatzia, and “The most beautiful drawing by Marina” (2006) by Katerina Papanikolopoulou and illustrated by Niki Leonidou. In the study of texts of children’s literature, space and time constitute an important parameter, since they both directly affect the young reader’s response.Firstly, we will refer to theoretical considerations on the narrative analysis of time and space, using a combination of methodological tools. We will examine the narrative techniques found in the texts, according to the theory of Genette, focusing on the time of narration, the sequence of events and the relationship between the time of history to the time of narration. We will also use the methodology proposed by the theory of Imagology, which we adapted taking into account the specificity of the texts under discussion of our analysis. In particular, we focused on the field of investigating the space of the “other”. Our aim is to identify and study the contrast noted when comparing the “familiar” space with the space of the “other”. This will offer us an analytical tool to detect evidence of racist ideology, which may help decode the stereotypical images that often acquaint the child reader with the world of the “different”. Illustrated books are considered very important and play a decisive role in shaping a child’s personality. Moreover, illustrated books often express the ideologies of authors and illustrators, directly or indirectly, consciously or unconsciously, as they carry ideas and ideological thesis.